2017
DOI: 10.2147/tcrm.s136125
|View full text |Cite
|
Sign up to set email alerts
|

Hollow viscus injuries: predictors of outcome and role of diagnostic delay

Abstract: IntroductionHollow viscus injuries (HVIs) are uncommon but potentially catastrophic conditions with high mortality and morbidity rates. The aim of this study was to analyze our 16-year experience with patients undergoing surgery for blunt or penetrating bowel trauma to identify prognostic factors with particular attention to the influence of diagnostic delay on outcome.MethodsFrom our multicenter trauma registry, we selected 169 consecutive patients with an HVI, enrolled from 2000 to 2016. Preoperative, intrao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The question on when to offer laparoscopy and whether to engage in a trial of non-operative management still remains unanswered. The combination of radiographic, laboratory, and physical examination findings was utilized in the Bowel Injury Prediction Score (23,28). The score of 2 or greater is highly suggestive of bowel injuries and may suggest early diagnostic laparoscopy; however, it was not used in this study and needs prospective validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question on when to offer laparoscopy and whether to engage in a trial of non-operative management still remains unanswered. The combination of radiographic, laboratory, and physical examination findings was utilized in the Bowel Injury Prediction Score (23,28). The score of 2 or greater is highly suggestive of bowel injuries and may suggest early diagnostic laparoscopy; however, it was not used in this study and needs prospective validation.…”
Section: Discussionmentioning
confidence: 99%
“…In most patients, only indirect signs of injuries can be identified, this can lead to missed injuries and delayed surgical treatment (20). A delay in surgical treatment of hollow viscus injuries in as little as 5 h may increase morbidity and mortality (2123). Despite its limitations, CT remains standard imaging of hemodynamically stable patients with BAT (8, 2427), and this study confirmed it.…”
Section: Discussionmentioning
confidence: 99%
“…There is still no consensus in the literature regarding the effects of delayed surgical treatment of traumatic small intestine perforation, but it is generally accepted that morbidity and mortality is significantly lower in the case of early diagnosis and emergency surgical treatment [21,22] Mingoli and colleagues found that leukocytosis and delayed treatment (>6 hours) are independent predictors of postoperative morbidity [26].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their rarity, experience with this injury is limited and no strong consensus exists in the literature regarding diagnosis and management of bowel injuries. [6,7] In penetrating trauma, early abdominal exploration is mandatory in 80% of cases and HVI diagnosis is prompt and easy. In blunt trauma, the non-operative management of solid organ injury has clearly increased the risk of delayed diagnosis and treatment of bowel lesions.…”
Section: Discussionmentioning
confidence: 99%